A comprehensive study on image segmentation - maruthi nagendra prasad, J.; M.VamsiKrishna, Dr. (International Journal of Engineering and Technology, 2018)
With the evolution of computing, there is an acceleration in the use of image processing techniques in various applications, image segmentation, a procedure in which images are divided into many segments and with this, itâ€™s possible to identify the region of interest from an image. The main idea of this comprehensive study is to present various existing segmentation techniques.Â Â Â Â